2019
DOI: 10.2147/cmar.s200318
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Meta-Analysis And Systematic Review Of Accuracy Of Endoscopic Ultrasound For N Staging Of Gastric Cancers</p>

Abstract: BackgroundEndoscopic ultrasonography (EUS) is widely used as a staging modality for gastric cancer. However, the results of studies on the use of EUS for N staging in gastric cancer vary. This study aimed at studying the overall diagnostic accuracy of EUS for N staging of gastric cancer.MethodsPublished studies were identified through searching the MEDLINE, Web of Science, EMBASE, SpringerLink and ScienceDirect databases. A bivariate random effect model was used to estimate the sensitivity, specificity, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…EUS is considered the key technique for layer tumor distribution in gastric cancer, which makes it the most important tool for T assessment. On the other hand, CT, due to its wide distribution is the first imaging technique used in many institutions for the assessment of gastric cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…EUS is considered the key technique for layer tumor distribution in gastric cancer, which makes it the most important tool for T assessment. On the other hand, CT, due to its wide distribution is the first imaging technique used in many institutions for the assessment of gastric cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis and systematic review showed that the sensitivity GC N staging using EUS is quite high (82%). But the specificity of EUS for the same N staging in GC was not as high (68%) (67).…”
Section: Gc Stagingmentioning
confidence: 94%
“…After obtaining the histology of the resected specimen, the probability of lymphatic dissemination may much more reliably than by imaging techniques (like conventional EUS[ 133 ]) just be predicted from a nomogram and scoring system derived from >10,000 Patients. [ 95 134 135 136 ] The therapeutic strategy after R0-ER of more advanced superficial cancers is by no means clear or easy.…”
Section: Is There a Role For Eus Miniprobes In N-staging In Early Gastric Cancers?mentioning
confidence: 99%